2014
DOI: 10.3109/10826084.2014.962661
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Drug Use, Risky Behavior, and Health Status Among Persons Who Inject Drugs Living in San Diego, California: A Latent Class Analysis

Abstract: Background Among persons who inject drugs (PWID), polydrug use (the practice of mixing multiple drugs/alcohol sequentially or simultaneously) increases risk for HIV transmission and unintentional overdose deaths. Research has shown local drug markets influence drug use practices. However, little is known about the impact of drug mixing in markets dominated by black tar heroin and methamphetamine, such as the western United States. Methods Data were collected through an ongoing longitudinal study examining dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 36 publications
3
42
0
3
Order By: Relevance
“…To reduce potential misclassification bias, we only included MTU variables as indicators where at least 15% of participants reported their use for inclusion in the LCA. 14 …”
Section: Methodsmentioning
confidence: 99%
“…To reduce potential misclassification bias, we only included MTU variables as indicators where at least 15% of participants reported their use for inclusion in the LCA. 14 …”
Section: Methodsmentioning
confidence: 99%
“…Injection drug use, a large red-light district (zona roja) attracting sex tourism, and high levels of social and economic disparities have contributed to a localized HIV epidemic in Tijuana. Given the substantial bidirectional traffic of people and goods in this region, there are significant implications for cross-border spread of unsafe injecting practices that heighten the risk of blood-borne infections, including HIV and hepatitis C. Although PWID are known to inject both heroin and methamphetamine (Darke & Hall, 1995;Garfein et al, 2013;Meacham et al, 2015;Roth et al, 2015;Rusch et al, 2009), less is known about the prevalence of and risks associated with mixed or co-injection of this depressant-stimulant combination.The present analysis examined the prevalence and correlates of heroin-methamphetamine co-injection among PWID in San Diego, California, and Tijuana, Baja California. Given the production of methamphetamine in Mexico and the limited access to healthcare and drug treatment services, we hypothesized that past-6-month prevalence of heroinmethamphetamine co-injection would be higher among PWID in Tijuana.…”
mentioning
confidence: 99%
“…Within samples, however, we found that latent classes with a higher number of substance use combinations have higher probabilities of risky injection behavior than classes characterized by fewer substances. The rural and urban classes characterized by primarily heroin injectors had the lowest probability of risky injection behavior, echoing results from PWID in Baltimore (Kuramoto et al, 2011) and San Diego (Roth et al, 2015). Conversely, the urban class that was characterized by high injection and non-injection polysubstance use had the highest probabilities of risky injection behavior, findings supportive of research among various samples of PWID (Harrell et al, 2012).…”
Section: Discussionmentioning
confidence: 63%
“…Response options ranged from (0) never to (9) four or more times per day. To differentiate between habitual use rather than episodic use (Roth et al, 2015), we dichotomized each item into (0) less than weekly use and (1) weekly or more use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation